AN ANALYSIS OF EDUCATION, UNEMPLOYMENT, AVERAGE CONSUMPTION PER CAPITA ON POVERTY IN NORTH SUMATERA, 2015 - Nainggolan, LoraEkana (JURNAL KEBANGSAAN, 2017)
Poverty is a problem faced by all countries in the world, especially developing countries such as Indonesia. Poverty is a measure of a countrys welfare, as measured by the powerlessness of a person to meet the minimum needs. In Indonesian poverty are unresolved issues with the reason that almost all Indonesian provinces have poverty rates over 10 percent. The object of this study is the North Sumatera Province which entitles âAn Analysis of Education, Unemployment, Average Consumption per Capita on Poverty in North Sumatera 2001-2013". The main objective of this study was to analyze the effect of education, unemployment, average consumption per capita on poverty in North Sumatera. The data used in this study is the secondary time series data from 2001 to 2013 obtained from BPS of North Sumatera. The method used in this study is Ordinary Least Square (OLS). The result shows the value of RÂ² of 0,9115, which means by 91,15 % the proportion of independent variables studied were able to explain the variation of the dependent variable in the model, while the remaining 8,85% explained by other variables that are not used in this study. This study shows the significant effect with the number of open unemployment, average consumption per capita to the number of poor people in North Sumatera. While the influence of the index of education not significant effect on the number of poor people in North Sumatera. The amount of effect is shown by the variable coefficient value - independent variables, namely: -0,3996 for the index of education, and 1,162 for a variable number of open unemployment, -2.3048 for the variable average consumption per capita. Keywords: Poverty, Index of Education, Amount of Open Unemployment, The Average Consumption per Capita